Shakespeare and the arts of language - McDonald, Russ, 1949- (Oxford Shakespeare topics., 2001)
Oxford Shakespeare Topics provide students and teachers with short books on important aspects of Shakespeare criticism and scholarship. Each book is written by an authority in its field, and combines accessible style with original discussion of its subject. Notes and a critical guide to further reading equip the interested reader with the means to broaden research. For the modern reader or playgoer, English as Shakespeare used it can seem alien and puzzling: vocabulary and grammar are in transition, pronouns and verb-forms can seem unfamiliar. Moreover, the conventions of poetic drama may also.